Scoring atonia during normal and pathological rapid eye movement sleep: Visual and automatic quantification methods. (26th February 2013) - Fulda, Stephany; Plazzi, Giuseppe; Ferri, Raffaele
Abstract: One of the essential features of rapid eye movement (REM) sleep behavior disorder is REM sleep without atonia seen during nocturnal polysomnographic recordings. In this paper we provide an overview about the varied scoring criteria proposed for visual analysis of loss of atonia during REM sleep. The automatic quantification of loss of atonia overcomes many of the limitations of visual scoring and these new approaches are reviewed. Finally, the contributions of these automatic methods to the understanding of the complex mechanisms underlying muscle atonia and motor suppression during REM sleep are briefly illustrated.